Bringing Islamic banks closer to the ideal: from debt-based financing to equity-based modes - Sadique, Muhammad Abdurrahman (2015)
Islamic banks in general employ murabahah-based structures to finance local and foreign trade transactions, albeit with a considerable level of inconvenience. Practical involvement in the field of Islamic banking would reveal that current equity structures, where implemented, comprise various areas that call for a reassessment in the light of shari‘ah principles. Many equity formats in vogue embody features that inhibit them from optimum performance. Profit and loss distribution in equity ventures is a fundamental issue that determines the outcome of Islamic equity financing modes and the extent of influence they could exert on directing the flow of wealth. In some variations of equity investment adopted by Islamic banks, the profit loss sharing mechanism is found to be correlated to the period of the facility in some manner, through ensuring an association between the profit ratio and the duration of investment. The mechanism employed by Islamic banks in deciding the ratio of profit sharing may require further refinement. Structures employed for project financing through equity participation could be further enhanced to reflect the essential aspects that differentiate them from interest-based modes.